Effects of the Danish saturated fat tax on the demand for meat and dairy products. Issue 17 (26th August 2015) - Jensen, Jørgen Dejgaard; Smed, Sinne; Aarup, Lars; Nielsen, Erhard
Abstract: Objective: Taxation of unhealthy food is considered a regulation tool to improve diets. In 2011 Denmark introduced a tax on saturated fat in food products, the first country in the world to do so. The objective of the present paper is to investigate the effects of the tax on consumers' intake of saturated fat within three different types of food product group: minced beef, regular cream and sour cream. Design: We use an augmented version of the Linearized Almost Ideal Demand System (LAIDS) functional form for econometric analysis, allowing for tax-induced structural breaks. Setting: Data originate from one of the largest retail chains in Denmark (Coop Danmark) and cover January 2010 to October 2012, with monthly records of sales volume, sales revenue and information about specific campaigns from 1293 stores. Results: The Danish fat tax had an insignificant or small negative effect on the price for low- and medium-fat varieties, and led to a 13–16 % price increase for high-fat varieties of minced beef and cream products. The tax induced substitution effects, budget effects and preference change effects on consumption, yielding a total decrease of 4–6 % in the intake of saturated fat from minced beef and regular cream, and a negligible effect on the intake from sour cream. Conclusions: The Danish introduction of a tax on saturated fat in food in October 2011 had statistically significant effects on the sales of fat in minced beef and cream products, but the tax seems to have reduced the beyond-recommendation saturated fat intake to only a limited extent.